Nature's Treasures - Hoare, Ben; McKean, Kaley (New York, NY : DK Publishing, 2021)
Nature is bursting with objects that are beautiful, useful, and intriguing. But where do they come from-- and what are they for? Hoare helps readers discover natural objects that have amazing tales to tell. From a delicate bird's feather to a glittering rock from space, readers will marvel at minerals forged through time, ingenious structures made by nature, and remarkable features that help animals and plants to survive and thrive. --
Introduction -- Nature's treasures -- Noticing nature -- Animals -- Plants, fungi, and algae -- Minerals and rocks -- Made by nature.
Keywords: Nature; Natural history; Animals; Plants; Minerals; Rocks; Nature; Nature -- Miscellanea; Natural history; Natural History; Minerals; Nature; Sciences naturelles; Minéraux.; Nature; natural sciences; mineral; JUVENILE NONFICTION / Science & Nature / Discoveries; Animals; Minerals; Natural history; Nature; Plants; Rocks; picture books; Picture books; Picture books; Livres d'images.